Evaluasi Program Penyediaan Air Bersih dan Sanitasi Berbasis Masyarakat (PAMSIMAS) di Desa Rowa Kabupaten Nagekeo - Desanvitores Elytilsa Panyol; Maria M. Lino; Belandina Liliana Long; Alfred Omri Ena Mau (Universitas Kristen Indonesia Toraja, 2026)
The Community-Based Drinking Water Supply and Sanitation Program (PAMSIMAS) is a government initiative intended to improve access to clean water and sanitation services in rural communities through community participation. This study aims to evaluate the implementation of the PAMSIMAS Program in Rowa Village, Boawae District, Nagekeo Regency, particularly in relation to program sustainability and service effectiveness. The research employed a descriptive qualitative approach using William N. Dunn’s policy evaluation model, which includes the indicators of effectiveness, efficiency, equity, and responsiveness. Data were collected through interviews, observation, and documentation involving village government officials, program managers, and community members as informants. The findings show that the program was initially effective in expanding access to clean water and reducing the burden of residents in obtaining water for daily needs. However, these benefits lasted for only about three years because of technical problems in the pumping system, solar panels, and supporting infrastructure. In terms of efficiency, program implementation was completed according to the planned schedule and budget allocation, but limited technical quality and weak managerial capacity affected long-term performance. The equity aspect indicates that water facilities and services were not distributed evenly across all hamlets, causing unequal access among community members. Meanwhile, community responses were generally positive, although concerns remained regarding service continuity, infrastructure maintenance, and water distribution. This study concludes that PAMSIMAS has contributed to improving clean water access in Rowa Village, but stronger institutional support, sustainable maintenance funding, active community participation, and program accountability are needed to ensure long-term overall service quality.